Propagation Model in Indoor and Outdoor for the LTE Communications - Sun-Kuk Noh; DongYou Choi (International Journal of Antennas and Propagation)
Rapidly rising demand for radio communication and the explosion in the number of mobile communications service subscribers have led to the need for optimization in the development of fifth-generation (5G) mobile communication systems. Previous studies on the development of propagation models considering a propagation environment in the existing microwave band have been mainly focused on analyzing the propagation characteristics with regard to large-scale factors such as path losses, delay propagation, and angle diffusions. In this paper, we investigated the concept of spatial and time changes ratios in the measurement of wave propagations and measured RSRP of Long Term Evolution (LTE) signals at three locations considering the time rate of 1% and 50%. We confirmed the concept of spatial and time changes rate based on the results of analyzing the signal data measured and proposed the propagation models 1 and 2 in microcell downtown. The forecast results using proposed models 1 and 2 were better than the COST231 model in both indoor and outdoor measured places. It was predicted between a time rate of 1% and 50% indoor within 400m and outdoor within 200m. In the future, we will study the propagation model of 5G mobile communication as well as the current 4G communication using artificial intelligence technology.